Dangerous decade Taiwan's security and crisis management - Taylor, Brendan 1974- (Adelphi series, 2019)
Taiwan's position looks increasingly precarious, and tensions threaten to grow into a major strategic crisis. Chinese President Xi Jinping has made reunification with Taiwan a central pillar of his vision for China, and has ramped up diplomatic and economic pressure on Taiwan. Its inhabitants are increasingly estranged from the mainland, and Tsai Ing-wen's administration refuses to conduct relations with China on Beijing's terms. Taiwan could take on renewed strategic significance amid the backdrop of the deepening rivalry between China and the United States, and find itself at the centre of a Cold War-style superpower confrontation. While Washington's support and military power has historically guaranteed Taiwan's security, this is no longer a certainty. This Adelphi book argues that China's military modernisation has changed the cross-strait military balance, and the ability of the US to prevail in a conflict over Taiwan may have evaporated by 2030. As China feels increasingly empowered to retake Taiwan, there is significant potential for escalation, particularly given the ambiguity of Beijing's red lines' on Taiwan. Neither Beijing, Taipei nor Washington want such a conflict, but each is challenging the uneasy status quo. Taylor calls for the introduction of a narrower set of formal crisis-management mechanisms designed to navigate a major Taiwan crisis